Legal Study on the Preservation of Traditional Weaving in North Lombok: Between Intellectual Property Rights and Communal Protection - Anam, Ahmad Gautsul; Paradina, Wanda (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
Traditional weaving from North Lombok represents intangible cultural heritage with significant economic and cultural value, yet faces threats of extinction and commercial exploitation without fair compensation. This research examines legal protection of traditional weaving through Intellectual Property Rights and communal protection regimes based on Law Number 28 of 2014 on Copyright and Government Regulation Number 56 of 2022 on Communal Intellectual Property. The research employs a normative juridical approach with analysis of laws and regulations and case studies in North Lombok. Findings reveal a dual protection system where the state holds copyright over traditional cultural expressions but has not optimally conducted inventory and economic benefit distribution to weaving communities. Main constraints include minimal documentation of weaving motifs, limited legal awareness among communities, and absence of clear benefit-sharing mechanisms. The research recommends accelerating inventory of North Lombok traditional weaving, strengthening weaving community institutions, and establishing specific regional regulations governing protection and economic utilization of weaving based on communal justice principles.